Molecular dynamics of thermoenzymes at high temperature and pressure: a review - Karjiban, Roghayeh Abedi; Lim, Wui Zhuan; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin (Springer, 2014)
Lipases are known for their versatility in addition to their ability to digest fat. They can be used for the formulation of detergents, as food ingredients and as biocatalysts in many industrial processes. Because conventional enzymes are frangible at high temperatures, the replacement of conventional chemical routes with biochemical processes that utilize thermostable lipases is vital in the industrial setting. Recent theoretical studies on enzymes have provided numerous fundamental insights into the structures, folding mechanisms and stabilities of these proteins. The studies corroborate the experimental results and provide additional information regarding the structures that were determined experimentally. In this paper, we review the computational studies that have described how temperature affects the structure and dynamics of thermoenzymes, including the thermoalkalophilic L1 lipase derived from Bacillus stearothermophilus. We will also discuss the potential of using pressure for the analysis of the stability of thermoenzymes because high pressure is also important for the processing and preservation of foods.